PENERAPAN TUTOR SEBAYA DISERTAI PENILAIAN PORTOFOLIODALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMPN 4 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Wati, Nila; Rahmi, Rahmi; Anggraini, Villia (Pendidikan Matematika, 2013)
The research was due to the lack of studentsâ activities and students were bit afraid of asking questions to the teacher, instead, the preferred asking to their peers. The research aimed at describing studentsâ activities during the implementation of peer Tutor with a Portfolio evaluation. It was to see whether the implementation better than conventional learning technique. The design was experimental research. The population was stucents grade VIII at SMPN 4 Pancung Soal. They were VIII1, VIII2, VIII3, VIII4. Using random sampling technique, grade VIII1 was chosen as the experimental group, while grade VIII2 as the control group. The instrument used was observation sheet and essay mathematic test. From the test reliability, the learning outcome of learning with the implementation of peer tutor with portfolio evaluation was obtained.Based on the analysis of observation sheet, there was an improvement of studentsâ activities during the teaching and learning process and the data analysis obtained was distributed homogeny and normal. Based on the analysis of hypothesis, it was obtained that the p-value= 0,012 was < Î±=0,05. Thus, the hypothesis was accepted. Therefore, it can be concluded thet studentsâ math concept understanding using peer tutor technique with a portfolio evaluation was better than that of conventional technique.